2018
DOI: 10.1111/beer.12181
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility towards human development: A capabilities framework

Abstract: The starting point of this paper is the need to promote a people‐centred corporate social responsibility (CSR) framework in a context where many human needs and rights remain unsatisfied and where businesses may have both a positive and a negative impact on the quality of life of human beings today and tomorrow and may even lead to irreversible damage. Our normative definition of CSR is consistent with the criteria established by the EU Commission in 2011. We conceive CSR as a responsibility towards human deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 81 publications
1
43
0
Order By: Relevance
“…Furthermore, governmental tax incentives and tax exemptions (Lu, 2013), across many of these countries also aim to engender a more proactive stance towards corporate community involvement by companies (See Table 1), potentially, as a more sustainable solution to poverty alleviation (Nugroho, Tanaya, Widiyanti, & Permana, 2010;Rahman et al, 2011). The disclosure of HR practices, could be attributed to the extensive labour policies prevalent across all six countries together with the other "soft" laws such as the United Nation Global Compact and the OECD principles (Renouard & Ezvan, 2018). Companies in the region therefore, seem to be focused on engaging in creating shared value through their HR practices (Battaglia, Bianchi, Frey, & Passetti, 2015;Holder-Webb, Cohen, Nath, & Wood, 2009;Kuasirikun & Sherer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, governmental tax incentives and tax exemptions (Lu, 2013), across many of these countries also aim to engender a more proactive stance towards corporate community involvement by companies (See Table 1), potentially, as a more sustainable solution to poverty alleviation (Nugroho, Tanaya, Widiyanti, & Permana, 2010;Rahman et al, 2011). The disclosure of HR practices, could be attributed to the extensive labour policies prevalent across all six countries together with the other "soft" laws such as the United Nation Global Compact and the OECD principles (Renouard & Ezvan, 2018). Companies in the region therefore, seem to be focused on engaging in creating shared value through their HR practices (Battaglia, Bianchi, Frey, & Passetti, 2015;Holder-Webb, Cohen, Nath, & Wood, 2009;Kuasirikun & Sherer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, scholars have tried to integrate (moral) competencies into context‐specific business domains that deal with sustainable development, for instance in the field of corporate social responsibility (Osagie et al, ; Renouard & Ezvan, ; Wesselink, Blok, Leur, Lans, & Dentoni, ) and the field of sustainable entrepreneurship (Lans et al, ; Ploum et al, ). Within these fields, two distinct moral competencies are highlighted: normative competence and (strategic) action competence.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Finally, as different authors have indicated (Griffin, ; Renouard & Ezvan, ), the analysis of how companies become involved in communities to improve human development should be promoted. These works indicate that studies about the community have become increasingly important in recent years, in line with the United Nations goals for Sustainable Development.…”
Section: Conclusion Limitations and Future Research Directionsmentioning
confidence: 99%
“…Finally, as different authors have indicated (Griffin, 2017;Renouard & Ezvan, 2018) The tables with regression analysis and the data used in this paper can be obtained in the following Zenodo community (https://zenodo.org/ communities/ccis/about/).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%